PROJECT BASED AND ENGLISH LANGUAGE LEARNING IN CROSS CULTURAL UNDERSTANDING CLASSES - Meita Lesmiaty Khasyar; Ayu Afriyani; Muhammad Syamsudin; Ana Ratnasari; Resya Fakhrunisa (Journal Fascho in Education Conference-Proceedings, 2021)
Culture is an important and interesting topic in the field of Teaching English as a Foreign Language. Culture and Language are interrelated and, therefore, it is essential that we understand the role of culture in education. Students’ culture will play a major role in their learning. The way students interact with their teachers, the way they respond to questions, the way they interact with others, the way they view education, and the way they value work are all factors that play a role in the learning process. Indeed, for EFL learners, cross culture understanding videos gives a double challenge as they should express their creative ideas in English. This paper, hence, shares ideas to engage students in activities and projects that increase their confidence and foster the motivation to explore the use of English creatively. It was offered as an exam project in English Education Department of STKIP Muhammadiyah Bogor, cross culture understanding project based learning aims at nurturing students’ creativity and confidence, as well as encouraging them to share their ideas about culture and how to explain it in English. Activities are designed in accordance with the course objectives to share information about cultural diversity, promote local culture and popular culture, and examine the influence of one’s culture on learning. Students also improve their language ability as they experiment with the English words, and English expression.